(untitled) (Nepal Journal of Epidemiology, 2014)
Background Ethnicity play a role in the occurrence of urinary stones, probably related to climatic, environmental and dietary factors in ethnic groups. The association between ethnicity, age, clinical profile, stone size with type of ureteric stones among males with urolithiasis was studied. Materials and Methods Male patients (>18 years) with lower ureteral stones size <10mm attending outpatient department of Urology, at a private hospital, Ajman over a period of one year were included. Ethics approval was obtained from Institutional Ethics Committee. Data was retrieved from the case records which included socio-demographic variables (age, ethnicity), clinical profile (ureteric colic, duration of pain, other complaints), and laboratory investigations (type of stone, stone size). Descriptive and inferential statistics were performed with SPSS-20 and p values <0.05 considered significant. Results 185 male patients were included. Mean age was 41.5 (7.3) years, range (22-71) years. Out of the total, 81 (43.8%) patients were Asians, 81(43.8%) Arabs and 23 (12.4%) were of other ethnicity. Most patients (95.1%) presented with ureteric pain. 49 (26.5%) had family history of stone disease where calcium oxalate monohydrate and uric acid stones were common, with majority being first degree relation. Data on stone type was available for 90 patients; of which, 21 were calcium oxalate monohydrate, 33-calcium oxalate dehydrate, 24-uric acid and remaining 12 other form of stones. Average age for different types of stone was 38.3, 41.6, 39.4 and 42.8 years for calcium oxalate monohydrate, calcium oxalate dehydrate, uric acid and other types respectively. Conclusion Uric acid stones were more prevalent among Asians and calcium oxalate-dehydrate stones among Arabs. Future studies can be conducted among multiethnic population focusing on dietary pattern and stone analysis. DOI: http://dx.doi.org/10.3126/nje.v4i4.11359 Nepal Journal of Epidemiology 2014; 4(4):393-98